LYMPHOCYTE RESPONSE TO Mycobacterium leprae ANTIGENS IN REVERSAL REACTION STATE OF LEPROSY - Yusuf, Irawan; Agusni, Indropo (Institute of Topical Disease Universitas Airlangga, 2015)
Reversal Reaction (RR) in Leprosy is a sudden inflammatory episode in the chronic course of the disease due to rapid change of cellular immunological status. The aim of the study is to measure the in vitro results of Lymphocyte Stimulation Index (LSI) RR leprosy derived lymphocytes after challenged with M.leprae antigens. Twenty three Borderline Leprosy with RR and 11 Borderline Leprosy patients without RR were included in the study. Peripheral Blood Mononuclear Cells (PBMC) were separated from peripheral blood of these patients using Ficol-Hypaque column and cultured in laboratory. Using the colorimetric tetrazole (MTT) method these lymphocytes were challenged with PHA, Dharmendra antigen (1/100 and 1/10 dilutions), LAM (50 and 100 nanograms). Stimulation Index were calculated and superanatans were collected for measuring the IFN-Î³ and IL-10 production (ELISA). All of lymphocytes from RR patients showed higher Stimulation Index after challenged with the five M.leprae antigens compared to lymphocytes from non RR patients (p <0.05) . IFN-Î³ and IL-10 also increased but not significant (p>0.05). It is concluded that lymphocytes of leprosy patients during RR state are more sensitive to antigenic stimuli compared to non-RR leprosy patients. Further extended studies are needed to determine the